Credibility of online reviews and initial online trust in hotel services: the roles of similarity and review quality - Kusumasondjaja, Sony; Shanka, Tekle; Marchegiani, Chris (Australian and New Zealand Marketing Academy, 2011)
As a new type of word-of-mouth media, online hotel review sites have a significant role in travelers’ decision making. Despite of growing popularity and adoption among travelers, online reviews are often questioned for their credibility. The purpose of this study is to investigate how review quality and perceived similarity affect travelers’ perception of credibility of the reviews and their initial trust in the hotel being reviewed. A survey involving 430 real travelers from 16 countries was conducted in popular tourist destination. Results confirm that (1) review quality affects credibility and initial trust in hotel services; (2) similarity affects credibility and initial trust in hotel services; (3) credibility of online reviews affects initial trust in hotel services.